The Management of Equality Education in Kejar Paket C Program (Equal to High School) - Labora, Elizabeth; Hidayat, Dayat (Universitas Negeri Semarang, 2022)
Historically, knowledge was introduced into the school curriculum to enable people, who entered the education level to study related subjects to gain some background knowledge to a higher level. This study aims to describe program management in kejar package C. This research is a descriptive study. The approach used is qualitative. The subjects of this study consisted of one manager, one tutor, and two learning residents. Data collection was carried out using observation, interviews, and documentation techniques. The techniques used in data analysis are data reduction, data display, and concluding. The results of this study indicate that planning uses problem identifiers, formulation of vision, mission and objectives, supporting and inhibiting factors, recruitment of tutors, learning residents, facilities/infrastructure, and costs. Organizing by distributing the tasks of managers, teachers, and learning residents. The learning implementation is carried out by preparing a learning implementation plan/syllabus, learning implementation is carried out twice a week, subjects, and complete learning resources are available, and face-to-face, tutorial, and independent learning activities. Supervision is carried out internally and externally. The assessment is carried out formatively and summatively